2015
DOI: 10.1109/jstars.2015.2398032
|View full text |Cite
|
Sign up to set email alerts
|

Scaling up to National/Regional Urban Extent Mapping Using Landsat Data

Abstract: This paper describes a methodology to extract a consistent human settlement extent layer using Landsat data and its implementation in the Google Earth Engine platform. The approach allows the extraction of human settlement extents by means of the existing Landsat 5 and 7 data sets, allowing to check their evolution at 30-m spatial resolution. Since human settlements are the main proxy to people geographical distribution and to building locations, this layer may serve as a mean to disaggregate people/building c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…With appropriate ground-truth data, GEE can serve as an accessible and feasible platform for image classification and analysis of large and geographically diverse regions. Though GEE has been used in previous studies for various applications, including population [70,75] and forest cover [76] mapping, ours is the first to provide comprehensive open-source ground-truth data that can serve as a training set for supervised classification of built-up land cover and for evaluation/validation of existing classifiers and classification products.…”
Section: Discussionmentioning
confidence: 99%
“…With appropriate ground-truth data, GEE can serve as an accessible and feasible platform for image classification and analysis of large and geographically diverse regions. Though GEE has been used in previous studies for various applications, including population [70,75] and forest cover [76] mapping, ours is the first to provide comprehensive open-source ground-truth data that can serve as a training set for supervised classification of built-up land cover and for evaluation/validation of existing classifiers and classification products.…”
Section: Discussionmentioning
confidence: 99%
“…However, applying the proposed method in areas with large differences in background environment still requires further discussion. In addition, Google Earth Engine (GEE) stores a large number of data from satellite images and other earth observation databases and provides sufficient computing power to process these data [57]. When the network environment allows, we will try to use this method to update urban land areas in large areas on the GEE platform.…”
Section: Discussionmentioning
confidence: 99%
“…We are, of course, not the first to face these challenges-the authors of references [16,[40][41][42] have all suggested solutions.…”
Section: Dealing With the Inevitable Instabilities Arising From Diffementioning
confidence: 99%